Fuzzy logic expert system for assessing the condition of the HV motor stator insulation system - Ilić, Denis M; Žarković, Mileta; Milić, Momčilo; Jovanović, Đorđe; Kališkić, Radmila; Stanojević, Nikola (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
During operation, the electrical insulation system (EIS) of high-voltage motors is exposed to various factors that can affect its accelerated aging. Timely knowledge of the actual state of the EIS is of great help in allocating funds for service activities and improving the reliability of the plant. The condition of the HV motor can be assessed to some extent by performing available electrical tests. A major shortcoming is the insufficiently precise and undefined criteria in the current standards, which introduces a potential error in the bias of the evaluators of the results. The paper will propose the use of a phase logic expert system for assessing the condition of EIS stators of HV motors based on the results of electrical measurements, with reference to all the benefits that automation of the process of assessment and analysis brings with it. The created expert system will fully rely on the criteria defined in the IS32 - Internal Standard of PE EPS.
Keywords: Fuzzy logic; HV motor; condition diagnostic